1087. Evaluation of Risk Factors for Infection among Patients Receiving Ibrutinib. (31st December 2020) - Tham, Kenneth; Prelewicz, Stacy; deHoll, Sara; Stephens, Deborah; Gomez, Carlos A
Abstract: Background: Ibrutinib is a small-molecule inhibitor of Bruton tyrosine kinase (BTK) approved for various B-cell malignancies and cGVHD. Rates of serious infection—defined as requiring hospitalization or parenteral antimicrobials— and invasive fungal infection (IFI) in patients on ibrutinib are as high as 11.4% and 4.2% respectively (Varughese T, et al. Clin Infect Dis 2018;67(5):687-92), which may be related to off-target inhibition of interleukin-2-inducible T-cell kinase or macrophage function. Methods: We retrospectively reviewed infection complications in patients receiving ibrutinib at our institution between 06/01/2014 and 08/31/2019, including patients who received single-agent or combination ibrutinib. In this study, serious infection was defined as above, or a diagnosis of pneumonia regardless of hospitalization or parenteral antimicrobial therapy. Logistic regression was used to identify risk factors. Results: Baseline characteristics of 134 included patients are in Table 1. Infection and serious infection occurred in 96 (72%) and 48 (36%) patients, respectively. When pneumonia was not included as a criterion for serious infection, the serious infection rate was 22%. Prior allogeneic stem cell transplant (allo-HSCT) (OR 4.50; 95% CI 1.19 – 17.00) and corticosteroid use (OR 5.42; 95% CI 1.49 – 19.82) were significant risk factors for serious infection without pneumonia (Table 2). Of 37 patients (28%) who received primary HSV/VZV prophylaxis with acyclovir, there was one case of suspected herpes zoster infection (3%). IFI developed in 7 patients (5%): 5 with Pneumocystis jirovecii pneumonia (PJP), 1 with invasive aspergillosis, and 1 with a filamentous fungus, species unknown. Other identified organisms are detailed in Figure 1. Classical risk factors for IFI, including diabetes, allo-HSCT, and concurrent corticosteroid use, were not significant predictors in this group. Table 1. Baseline Characteristics Table 2. Risk Factor Analysis Figure 1. Identified Organisms in Serious Infection Conclusion: Serious infections developed at a higher rate than previously reported in the literature, with IFI rates similar to those previously described. Prior allo-HSCT and steroid use were found to be risk factors for serious infection without pneumonia. Treating physicians should have a high index of suspicion for pneumonia, IFI, and PJP in this population. Disclosures: All Authors : No reported disclosures